Canon EOS 70D : from snapshots to great shots - Young, Nicole S. (Peachpit Press, 2014)
Provides information on the features of the Canon EOS 70D camera, covering such topics as shooting modes, landscape and nature photography, taking portraits, action photography, lighting, and composition.